IMF Staff papers : Volume 40 No. 4. (IMF Staff Papers; IMF Staff Papers, 1993)
This paper uses microeconomic panel data to examine differences in the cyclical variability of employment, hours, and real wages for skilled and unskilled workers. Contrary to conventional wisdom, it finds that, at the aggregate level, skilled and unskilled workers are subject to the same degree of cyclical variation in wages. However, the quality of labor input is found to rise in recessions, inducing a countercyclical bias in aggregate measures of the real wage. The paper also finds substantial differences across industries in the cyclical variation of employment, hours, and wage differentials, indicating important interindustry differences in labor contracting.